DYNAMICS OF LEFT VENTRICULAR PARAMETERS IN THE LONG-TERM TREATMENT OF RENAL PARENCHYMATOUS ARTERIAL HYPERTENSION - N. Yu. Borovkova; N. N. Borovkov; Yu. A. Khor’kina; E. O. Obukhova; A. I. Arshinova (Кардиоваскулярная терапия и профилактика)
Aim. To investigate the dynamics of left ventricular (LV) parameters during the long-term treatment of renal parenchymatous arterial hypertension (RPAH) in patients with primary chronic glomerulonephritis and preserved renal function.Material and methods. The long-term follow-up included 136 RPAH patients with preserved renal function. Clinical assessment of blood pressure (BP) levels, 24-hour BP monitoring, and Doppler echocardiography (EchoCG) were performed at baseline and during the complex antihypertensive therapy (AHT) and pathogenetic therapy of RPAH patients. The treatment-related dynamics of LV structure and function was evaluated.Results. The long-term complex treatment of RPAH patients resulted in significantly reduced clinical BP levels, improved 24-hour BPM parameters, LV hypertrophy (LVH) regression, and improved diastolic and systolic LV function.Conclusion. The long-term complex AHT, in combination with pathogenetic therapy, resulted not only in reduced BP levels and improved circadian BP profile, but also in improved diastolic and systolic LV function and LVH regression among RPAH patients with preserved renal function.